Perancangan Kendali Tegangan Dc-Dc Converter Berbasis Arduino Untuk Pembangkit Listrik Tenaga Bayu - Wisanta, Hosea; Rajagukguk, Antonius (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Wind Energy Power Plant is a type of renewable energy utilization. This plant has low emissions and is environmentally friendly. The principle of this energy is to convert wind energy into electrical energy with an electric generator rotated by a wind turbine. The problem with this energy is that the output from the generator is not always constant because of the changing nature of the wind. In addition, this generator has a low efficiency value. Therefore, the authors conducted research by designing a voltage control using by DC-DC converter. This voltage control is designed using two buck converters that run the Maximum Power Point Tracking (MPPT) based on the Perturb and Observe (P&O) algorithm and the voltage regulator algorithm which is controlled using the Arduino. The MPPT algorithm is used to find the highest power value in the generator so that it can increase power efficiency. The voltage regulator algorithm serves to maintain the voltage value at 12 volts. This research was conducted with a simulation method that was validated by the tool. In this study, it was found that the MPPT algorithm and the voltage regulator worked well. The overall efficiency of designed tool is 79.43% for the simulation and 43.41% for the actual tool. Keyword : Wind Turbine, DC-DC Converter, MPPT, Voltage Regulator